The Occurrences of Gelatinous Drop-Like Corneal Dystrophy within an Acehnese Family - Samira, Cut Putri; Akbar, Muhammad Khalil; Islami, Dian (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2024)
Introduction: Gelatinous drop-like dystrophy (GDLD) presents as an infrequent form of corneal dystrophy characterized by an autosomal recessive inheritance pattern. While its incidence in Japan stands at roughly 1 in 33,000 individuals, it manifests less frequently in other populations. Surgical intervention, such as lamellar or penetrating keratoplasty is typically necessary to relieve symptoms Objective: To describe 3 cases of Gelatinous drop-like dystrophy and their treatment approaches Illustration: Three brothers were diagnosed with corneal dystrophy, marked by a white-yellow nodular lesion resembling a kumquat on the corneal surface. Each patient exhibited light perception with good projection in terms of visual acuity. All underwent full-thickness lamellar keratoplasty for treatment. A month post-surgery, their visual acuity had improved to 3/60, 2/60, and 2/60, respectively. Conclusion: GDLD is a rare corneal condition associated with potential vision loss. Identification through familial history, corneal clinical features and involvement contributes to diagnosing GDLD. Full-thickness penetrating keratoplasty may be considered for managing significant visual impairment resulting from GDLD Keywords: corneal dystrophy, full-thickness penetrating keratoplasty, gelatinous drop-like